THE NATURE, CAUSES AND CONSEQUENCES OF THE HIDDEN ECONOMY AND FACTORS AFFECTING IT (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article examines the scientific views of experts on the causes of the secret economy and the factors affecting it, the theoretical views on the economic, social and legal problems that create the secret economy and their consequences are highlighted. If we take into account the existence of a hidden economy in all countries and the negative and positive aspects that it can show to the country's economy, we will consider.